The First Confirmed Record of ShikraAccipiter badius (Gmelin, 1788) in Iraq - Mudhafar A. Salim; Salwan Abed; Zaman Salman Harbi (Al-Qadisiyah Journal of Pure Science, 2020)
Over the period of 2015-2020, and during the series of the field surveys arranged and conducted by the Iraqi Organization for Conservation of Nature (IOCN) in various locations and habitats in Iraq, IOCN team had the opportunity to survey various areas within Iraq in different seasons where new observations of bird species were made as the first records for Iraq; additionally, the team have also discovered new breeding evidences and expansions within different habitats in Iraq. During one of these surveys is central Iraq, specifically at the Middle Euphrates region, an individual of Shikra Accipiter badius was observed in the extreme north of Al-Qadisiyah province, Ad-Daghara sub-district. This paper confirms, through the details of the observation and description provided below, the first confirmed record of this species for Iraq.